Nutritional behavior and feeding profile of dairy production in cultivated pastures (Panicum maximum Jacq) - Núñez Delgado, Jimny (2019)
Variables inherent to the forage and animal component were evaluated to design feed profiles of dual-purpose cows grazing Panicum maximum Jacq in a dairy farm in the Peruvian tropics. The forage variables were growth rate and forage availability and the animal variables were the chemical composition of the diet and feed profile. The experiment was carried out in the dry, early rainy and rainy seasons. Fourteen enclosures were installed in 41.9 ha and five Brown Swiss x Creole lactating cows were used. Forage growth and availability rates were obtained through cutting and manual separation, diets were obtained by manual simulation, energy requirement through the budget of activities and feed profile through the balance of forage demand and supply. A completely randomized design was used for forage growth and availability, and random blocks for chemical composition. The forage growth rate varied between 8.16 and 46.28 kg DM/ha/day; forage availability between 2696.9 and 7764.3 kg DM/ha for the dry and rainy seasons, respectively. The concentration of metabolizable energy in the forage was 3.94 and 5.23 ME MJ/kg MS and total energy demand of cows was 102.0 and 90.1 MJ ME/ day for the dry and rainy seasons, respectively. Feed profile revealed a surplus in the rainy season and a deficit in the dry and early rainy seasons. It is concluded that the farm is underutilizing the pasture, especially in the rainy season, due to good forage availability and low stocking rate.